The Influence of CO2 and Exercise on Hypobaric Hypoxia Induced Pulmonary Edema in Rats - Sheppard, Ryan L.; Swift, Joshua M.; Hall, Aaron; Mahon, Richard T. (Frontiers in Physiology, 2018)
Abstract Individuals with a known susceptibility to high altitude pulmonary edema (HAPE) demonstrate a reduced ventilation response and increased pulmonary vasoconstriction when exposed to hypoxia. It is unknown whether reduced sensitivity to hypercapnia is correlated with increased incidence and/or severity of HAPE, and while acute exercise at altitude is known to exacerbate symptoms the effect of exercise training on HAPE susceptibility is unclear. Purpose: To determine if chronic intermittent hypercapnia and exercise increases the incidence of HAPE in rats. Methods: Male Wistar rats were randomized to sedentary (sed-air), CO2 (sed-CO2,) exercise (ex-air), or exercise + CO2 (ex-CO2) groups. CO2 (3.5%) and treadmill exercise (15m/min, 10% grade) were conducted on a metabolic treadmill, 1hr/day for 4 weeks. Vascular reactivity to CO2 was assessed after the training period by rheoencephalography. Following the training period, animals were exposed to hypobaric hypoxia (HH) equivalent to 25,000ft for 24 hrs. Pulmonary injury was assessed by wet/dry weight ratio, lung vascular permeability, bronchoalveolar lavage (BAL), and histology. Results: HH increased lung wet/dry ratio (HH 5.51±0.29 vs. sham 4.80±0.11, P < 0.05), lung permeability (556±84u/L vs. 192±29u/L, P < 0.001), and BAL protein (221±33µg/ml vs. 114±13 µg/ml, P < 0.001), white blood cell (1.16±0.26 vs. 0.66±0.06, P < 0.05), and platelet (16.4±2.3, vs. 6.0±0.5, P < 0.001) counts in comparison to normobaric normoxia. Vascular reactivity was suppressed by exercise (-53% vs sham, P < 0.05) and exercise+CO2 (-71% vs sham, P < 0.05). However, neither exercise nor intermittent hypercapnia altered HH-induced changes in lung wet/dry weight, BAL protein and cellular infiltration, or pulmonary histology. Conclusion: Exercise training attenuates vascular reactivity to CO2 in rats but neither exercise training nor chronic intermittent hypercapnia affect HH- induced pulmonary edema.